Business Innovation for the Post-pandemic Era in Vietnam - Thuan, Nguyen Hoang; Nguyen, Hung.; Pham, Hiep Cong.; Halibas, Alrence (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book documents the recent post-pandemic era business innovation research in Vietnam bringing together selected works from the 2022 'International Conference on Business Innovation: Business Innovation in a Post-pandemic World' held at RMIT University in Vietnam. The book contributes to the body of knowledge in several ways. It serves as a comprehensive reference for business innovation research and promotes recent progress in business innovation applications in Vietnam and offers a shared understanding to help coordinate future research in the field. .
Introduction to Business Innovation in the Post-pandemic Era in Vietnam: Digitalization and Smart Logistics -- Important Negotiation Behaviours in Entrepreneurs' New Product Launching Stage During Post-Covid-19 Era -- Does digital transformation increase efficiency in business? Evidence from Vietnam during the COVID-19 pandemic -- COVID-19 Disruption Risk - A Game-changing Factor for SMEs Digital Supply Chain Transformation.
Keywords: Technological innovations; Financial engineering; Business; Asia; Telemarketing; Internet marketing; Innovation and Technology Management; Financial Technology and Innovation; Asian Business; Digital Marketing